Influence of Joint Flexibility on Vibration Analysis of Free-Free Beams - Gunda Jagadish Babu; Krishna Y. (Nonlinear Engineering, 2014)
In present work, joint flexibility (or looseness) of the free-free beam is investigated by using a two noded beam finite element formulation with transverse displacement and joint rotations as the degrees of freedom per node at joint location. Flexibility of the joint is primarily represented by means of a rotational spring analogy, where the stiffness of the rotational spring characterizes the looseness of the flexible joint for an applied bending moment. Influence of joint location as well as joint stiffness on modal behavior of first five modes of slender, uniform free-free beams are discussed for various values of non-dimensional rotational spring stiffness parameter. Numerical accuracy of the results obtained from the present finite element formulation are validated by using the commercially available finite element software which shows the confidence gained on the numerical results discussed in the present study.